Dynamic response to peripheral nerve injury detected by in situ hybridization of IL-6 and its receptor mRNAs in the dorsal root ganglia is not strictly correlated with signs of neuropathic pain - Brázda, Václav; Klusáková, Ilona; Hradilová Svíženská, Ivana; Dubový, Petr (Molecular pain, 2013)
BACKGROUND: IL-6 is a typical injury-induced mediator. Together with its receptors, IL-6 contributes to both induction and maintenance of neuropathic pain deriving from changes in activity of primary sensory neurons in dorsal root ganglia (DRG). We used in situ hybridization to provide evidence of IL-6 and IL-6 receptors (IL-6R and gp130) synthesis in DRG along the neuraxis after unilateral chronic constriction injury (CCI) of the sciatic nerve as an experimental model of neuropathic pain. RESULTS: All rats operated upon to create unilateral CCI displayed mechanical allodynia and thermal hyperalgesia in ipsilateral hind paws. Contralateral hind paws and forepaws of both sides exhibited only temporal and nonsignificant changes of sensitivity. Very low levels of IL-6 and IL-6R mRNAs were detected in naïve DRG. IL-6 mRNA was bilaterally increased not only in DRG neurons but also in satellite glial cells (SGC) activated by unilateral CCI. In addition to IL-6 mRNA, substantial increase of IL-6R mRNA expression occurred in DRG neurons and SGC following CCI, while the level of gp130 mRNA remained similar to that of DRG from naïve rats. CONCLUSIONS: Here we evidence for the first time increased synthesis of IL-6 and IL-6R in remote cervical DRG nonassociated with the nerve injury. Our results suggest that unilateral CCI of the sciatic nerve induced not only bilateral elevation of IL-6 and IL-6R mRNAs in L4-L5 DRG but also their propagation along the neuraxis to remote cervical DRG as a general neuroinflammatory reaction of the nervous system to local nerve injury without correlation with signs of neuropathic pain. Possible functional involvement of IL-6 signaling is discussed.
Keywords: hybridizace in situ; modely nemocí na zvířatech; RNA, Messenger; Male; Rats, Wistar; receptory interleukinu-6; Sciatic Neuropathy; spinální ganglia; Neuralgia; Interleukin-6; In Situ Hybridization; mužské pohlaví; potkani Wistar; nemoci sedacího nervu; krysa rodu Rattus; Animals; interleukin-6; zvířata; Rats; Disease Models, Animal; Receptors, Interleukin-6; neuroglie; Neuroglia; Ganglia, Spinal; messenger RNA; neuralgie